Transboundary water disputes : state conflict and the assessment of their adjudication - Kornfeld, Itzchak E. (Cambridge : Cambridge University Press, 2019)
One of the most challenging aspects of climate change has been the increased pressure on water resources limited by droughts and new rain patterns, which has been exacerbated by rapid modernization. Due to these realities, disputes across national borders over use and access to water have now become more commonplace. This study analyzes the history and adjudication of transboundary water disputes in five international courts and tribunals, two US Supreme Court cases, and boundary water disputes between the United States and Canada and the United States and Mexico. Explaining the circumstances and outcomes of these cases, Kornfeld asks how effective the courts and tribunals have been in adjudicating them. What kind of remedies have they fashioned and how have they dealt with polycentric and sovereignty issues? This timely work examines the doctrine of equitable allocation of transboundary water resources and how this norm can be incorporated into international law.
Online resource; title from PDF title page (EBSCO, viewed March 4, 2019)
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Water -- Law and legislation; Water rights; Riparian rights; Water rights (International law); Rivers -- Law and legislation; Interstate controversies -- United States; United States -- Boundaries -- Canada; Canada -- Boundaries -- United States; United States -- Boundaries -- Mexico; Mexico -- Boundaries -- United States; Droits sur les eaux; Droits des riverains; Droits sur les eaux (Droit international); Controverses entre États fédérés -- États-Unis.; États-Unis -- Frontières -- Canada; Canada -- Frontières -- États-Unis.; États-Unis -- Frontières -- Mexique; water rights; riparian rights; LAW -- International; Boundaries; Interstate controversies; Riparian rights; Rivers -- Law and legislation; Water -- Law and legislation; Water rights; Water rights (International law); Canada; Mexico; United States